A study of the documentation strategy of the Argao Tourism Commission (ATC) in safeguarding the Argao's cultural heritage - Alcazar, Melissa A.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study was conducted to find out how far the Argao Tourism Commission (ATC) has gone in keeping and safeguarding the valuable and enduring cultural heritage collection of Argao through the programs they created, with special attention to their documentation strategy. The Municipality of Argao, which is located in the Cebu province, established the Argao Tourism Commission under Resolution No. 39 and Local Ordinance No. 17, with the aim of identifying and preserving the cultural heritage of Argao.
Based on the findings gathered through the interviews, ocular inspections, and survey questionnaires, the study revealed that there is a need to formulate a documentation strategy appropriate for this cultural heritage found in Argao. There is also a need to address other problems that exist in ATC. These are the budgetary constraints, proper training of staff, improvement of safeguarding practices, and a clear definition of ATC's duty/role.
The study therefore provided recommendations on the formulation of a documentation strategy using the formula designed by H. W. Samuels, the implementation of basic preservation practices for tangible and intangible heritage, and the improvement of all other duties such as the training of staff, promoting public awareness, designing exhibits, and allocating sufficient budget. These recommendations are researched and collated from reliable sources in order to help ATC attain its mission-vision-objectives.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Argao Tourism Commission (ATC), Documentation; Cultural property -- Philippines -- Cebu